2018
DOI: 10.2147/ijn.s167958
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oral absorption of pemetrexed by ion-pairing complex formation with deoxycholic acid derivative and multiple nanoemulsion formulations: preparation, characterization, and in vivo oral bioavailability and anticancer effect

Abstract: ObjectiveThe current study sought to design an oral delivery system of pemetrexed (PMX), a multitargeted antifolate antimetabolite, by enhancing its intestinal membrane permeability.Materials and methodsPMX was ionically complexed with a permeation enhancer such as Nα-deoxycholyl-l-lysyl-methylester (DCK) and prepared as an amorphous solid dispersion by mixing with dispersants such as 2-hydroxypropyl-beta-cyclodextrin (HP-beta-CD) and poloxamer 188 (P188), forming an HP-beta-CD/PMX/DCK/P188; the complex was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…In the twenty years since Meyer and Manning's classic 1998 review, 1 hydrophobic ion pairing (HIP) has gained prominence as a useful strategy for making charged hydrophilic molecules into hydrophobic complexes. The technique has a number of applications and has been used, among others, to dissolve molecules in supercritical CO 2 , 2 dissolve enzymes in organic solvents without losing activity, 3 improve intestinal adsorption [4][5][6] or skin permeation, 7,8 or otherwise enhance bioavailability. 9 This review will focus on one of the most prevalent uses of hydrophobic ion pairing: the complexation and encapsulation of charged hydrophilic small molecule, peptide, or protein therapeutics into drug delivery vehicles.…”
Section: Introduction Overview and Terminologymentioning
confidence: 99%
“…In the twenty years since Meyer and Manning's classic 1998 review, 1 hydrophobic ion pairing (HIP) has gained prominence as a useful strategy for making charged hydrophilic molecules into hydrophobic complexes. The technique has a number of applications and has been used, among others, to dissolve molecules in supercritical CO 2 , 2 dissolve enzymes in organic solvents without losing activity, 3 improve intestinal adsorption [4][5][6] or skin permeation, 7,8 or otherwise enhance bioavailability. 9 This review will focus on one of the most prevalent uses of hydrophobic ion pairing: the complexation and encapsulation of charged hydrophilic small molecule, peptide, or protein therapeutics into drug delivery vehicles.…”
Section: Introduction Overview and Terminologymentioning
confidence: 99%
“…Labrasol exhibits a high tolerance and promotes absorption through tight junctions in the absence of intestinal membrane damage [41,42]. A previous study confirmed that a molecular dispersion of PMX and DCK exists as an amorphous inclusion complex, enhancing the intestinal membrane permeability of PMX [29]. Thus, incorporation of Labrasol and P188 into our formulation may enhance micellar stability, control particle size, and facilitate intestinal absorption of PMX/DCK by allowing the material to accumulate to high levels on the intestinal surface.…”
Section: Resultsmentioning
confidence: 99%
“…The plasma concentration of PMX was determined using liquid chromatography/mass spectrometry (LC/MS), as described previously [29]. In brief, the plasma samples were defrosted and centrifuged at 2500× g for 5 min at 4 °C and mixed with 300 µL of 2% NH 4 OH in water along with 100 µL of standard solution or plasma sample and 10 µL of 4-[ N -(2,4-diamino-6-pterinidinylmethyl)- N -methylamino]benzoic acid hemihydrochloride hydrate (DAMPA; 5 µg/mL, IS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies indicate that nanoemulsion has a significant potential to increase the permeability of drugs. The proposed mechanisms were based on surfactant induced structural and fluidity changes in the membranes 24,25. IPC-NEs combined phospholipid complex technique with nanoemulsion system, exhibited synergic effect of nanoemulsion and IPC on the transport properties of insulin across the Caco-2 cell monolayers.…”
Section: Resultsmentioning
confidence: 99%